Effectiveness of Chloral Hydrate on Brain MRI in Children with Developmental Delay/Intellectual Disability Comparing with Normal Intelligence: Single Tertiary Center Experience - Ja Un Moon; Ji Yoon Han (MDPI AG, 2021)
Neurodiagnostic investigation requirements are expanding for diagnostic and therapeutic purposes in children, especially in those with developmental delay/intellectual disability (DD/ID). Thus, determination of optimal sedatives to achieve successful sedation and immobility without further neurological compromise is important in children with DD/ID. The purpose of this study is to assess the effectiveness and adverse reactions of chloral hydrate (CH) for brain magnetic resonance imaging (B-MRI) in children with DD/ID compared to those with normal intelligence (NI). We performed a retrospective chart review of children aged from 1 day to 12 years who required elective sedation using CH for B-MRI. About 730 cases (415 with DD/ID and 315 with NI) of CH sedation were conducted for B-MRI. Children with DD/ID showed a higher failure rate (22%) than did those with NI (6%); additional CH and prolonged sedation time were required. There was no difference in incidence of adverse reactions between DD/ID and NI groups (p = 0.338). Older or heavier children with DD/ID (p = 0.036 and p = 0.013, respectively), as well as those diagnosed with epilepsy or neuropsychiatric disorders showed higher risk of sedation failure (p < 0.001 for each). In conclusion, CH was a suboptimal sedative drug for children with DD/ID compared with those with NI. Other alternative or supplementary sedatives should be taken into consideration especially for those vulnerable groups.